Derepression of c‐Fos caused by MicroRNA‐139 down‐regulation contributes to the metastasis of human hepatocellular carcinoma. (23rd September 2012) - Fan, Qin; He, Minyi; Deng, Xinjun; Wu, William K. K.; Zhao, Liang; Tang, Jing; Wen, Ge; Sun, Xuegang; Liu, Yawei
Abstract : This study investigates whether the anti‐metastasis effect of microRNA‐139 (miR‐139) on hepatocellular carcinoma (HCC) is mediated through regulating c‐fos expression. The expression levels of miR‐139 and c‐fos in human HCC cell sublines with high (MHCC97H) and low (MHCC97L) spontaneous metastatic potentials were quantified using QPCR or Western blot. miR‐139 mimics was transfected into MHCC97H cells to overexpress miR‐139, and miR‐139 inhibitor was transfected into MHCC97L cells to down‐express miR‐139. The effect of overexpression or down‐expression of miR‐139 on c‐fos expression of MHCC97H and MHCC97L cells was evaluated using QPCR and Western blot. The 3′ untranslated region segments of FOS containing the miR‐139 binding sites were amplified by PCR, and the luciferase activity in the transfected cells was assayed. In comparison with the expression level of miR‐139 in MHCC97L cells, the expression level in MHCC97H cells was significantly decreased, whereas c‐Fos was significantly up‐regulated in MHCC97H. The overexpression of miR‐139 significantly inhibited the expression of c‐fos in MHCC97H cells, and the down‐expression of miR‐139 significantly promoted the expression of c‐fos in MHCC97L cells. miR‐139 suppressed the luciferase activity of the pGL‐FOS by approximately 40% compared with the negative control. In vitro cell migration analysis demonstrated that depletion of c‐fos or overexpression of miR‐139 in MHCC97H cells reduced cell migration, whereas overexpression of c‐fos or depletion of miR‐139 in MHCC97L cells increased cell migration. Thus, we got the conclusion that miR‐139 expression is down‐regulated in human HCC cell sublines with high spontaneous metastatic potentials (MHCC97H). Derepression of c‐Fos caused by miR‐139 down‐regulation contributes to the metastasis of HCC. Copyright © 2012 John Wiley & Sons, Ltd.